The role of financial technology in supporting access to financial inclusion in Algeria - Bakhtaoui, Fatima Zohra (International journal of economic perspectives, 2025)
This study aims to measure the role of Financial Technology (FinTech) in supporting access to financial inclusion in Algeria through a statistical analysis of a sample consisting of 131 individuals who are clients of financial institutions in Algeria. The study relied on an electronic questionnaire and found that FinTech is applied in the financial services provided, and that these services are characterized by financial inclusion from the perspective of the sample participants. The study also found that FinTech contributes to supporting access to financial inclusion by 49%. At the level of its dimensions, FinTech contributes to access to financial services by 42.6%, increases the use of financial services by 40.2%, and helps improve the quality of financial services by 27.5%.